Interrogating the construct of aviation English: Feedback from test takers in Korea. (April 2015) - Kim, Hyejeong; Elder, Catherine
This paper explores the underlying construct of both the English proficiency test for pilot and air traffic controller radiotelephony communication developed and administered in Korea and the ICAO language proficiency testing policy on which the test in Korea is based. It does so by canvassing the opinions of Korean airline pilots and air traffic controllers through 400 questionnaire and 22 interview sources. Results reveal a lack of fit between the policy construct and the reality through which the goals and objectives of the policy are accomplished and strong disapproval of the ICAO's espoused construct and the associated Korean English test from language users in the target domain. This study confirms the importance of eliciting views from such stakeholders (i.e., domain experts) who are well-placed to determine what really matters for communicative success in the context of concern.